The inhibition of ABCB1/MDR1 or ABCG2/BCRP enables doxorubicin to eliminate liver cancer stem cells - Wang Yin (Nature Portfolio, 2021)
Abstract Two ATP-binding cassette transporters, ABCB1/MDR1 and ABCG2/BCRP, are considered the most critical determinants for chemoresistance in hepatocellular carcinoma. However, their roles in the chemoresistance in liver cancer stem cells remain elusive. Here we explored the role of inhibition of MDR1 or ABCG2 in sensitizing liver cancer stem cells to doxorubicin, the most frequently used chemotherapeutic agent in treating liver cancer. We show that the inhibition of MDR1 or ABCG2 in Huh7 and PLC/PRF/5 cells using either pharmacological inhibitors or RNAi resulted in the elevated level of intracellular concentration of doxorubicin and the accompanied increased apoptosis as determined by confocal microscopy, high-performance liquid chromatography, flow cytometry, and annexin V assay. Notably, the inhibition of MDR1 or ABCG2 led to the reversal of the chemoresistance, as evident from the enhanced death of the chemoresistant liver cancer stem cells in tumorsphere-forming assays. Thus, the elevation of effective intracellular concentration of doxorubicin via the inhibition of MDR1 or ABCG2 represents a promising future strategy that transforms doxorubicin from a traditional chemotherapy agent into a robust killer of liver cancer stem cells for patients undergoing transarterial chemoembolization.